Colères des temps et réfugiés climatiques : pour une approche sociologique - Serge Dufoulon (VertigO)
Climatic question became a recent object of the sociology of the environment and the risks, and more exactly the question of the migrants or taken climatic refugees on whom so little was written. In what this population of migrants is so different of the other migrants' categories? Why States do not wish to grant them refugees' status? By trying to answer these questions it seems obvious to put the way the experts of the sociology of which approach the domain of the environment.